The Implementation Of Metacognitive Strategy To Enhance Students’ Critical Reading Ability - Lestari, Febrika Dwi; Sinaga, Nenny Triana; Simarmata, Rina Octavia; Simbolon, Desi (Jurnal Ilmu Sosial Mamangan, 2025)
It is a universal agreement among scientists that critical reading skill is one of the hardest skill that should be possessed by the student. Meanwhile, there is a prove claimed that the metacognitive strategy gave a major significance in reading ability. This study was intended to discover the use of metacognitive strategy in enhancing students’ critical reading skill. The subject of this study was the students of Nommensen HKBP University. This study applied the reading test and the observation sheets in two different cycles to observe the significant improvement of the students in their critical reading ability. The results showed the improvement of the students’ reading test score during the implementation of the two cycles. Furthermore, the observation sheets showed that the students was becoming interesting and easier in doing the critical reading practice and test that leading the class to comprehend the critical reading skill successfully. Therefore, it is apparent that through the implementation of the metacognitive strategy, students can improve their understanding in the critical reading skill.